Novel Molecular Type of Clostridium difficile in Neonatal Pigs, Western Australia - Squire, Michele M. (Centers for Disease Control and Prevention, 2013)
Clostridium difficile causes neonatal enteritis in piglets; strains of PCR ribotype 078 are most commonly identified. We investigated C. difficile prevalence in piglets in Australia and isolated a novel strain with a unique pathogenicity locus. In a mouse infection model, this strain produced more weight loss than did a ribotype 078 strain.